Accuracy of Capillary Glucose Testing in Gestational Diabetes Screening - Arisa Kongcharoensukying; Boonlert Viriyapak; Dittakarn Boriboonhirunsarn (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives:To assess the accuracy of capillary whole blood glucose compared to conventional venous plasma glucose testing for 50-g GCT in gestational diabetes mellitus (GDM) screening.Materials and Methods: A total of 180 women at-risk for GDM were randomly selected and enrolled and a 50-g GCT was offered as a screening test. At 1 hour after glucose loading, a capillary glucose testing was performed by well-trained nurses using a Nova Biomedical StatStrip®. Within 5 minutes after capillary glucose test, venipuncture was then performed by certified technicians and venous blood was sent to a certified central laboratory to determine plasma glucose value. Results from POCT glucose testing were compared with venous plasma glucose (gold standard) to evaluate for its accuracy. Women with venous plasma glucose ≥ 140 mg/dL were offered 100-g OGTT for GDM diagnosis according to current guideline.Results: Mean age was 33.1 years and 53.9% were nulliparous. Common GDM risks were age ≥ 30 years (87.8%), family history of DM (32.2%), and BMI ≥ 25 kg/m2 (25%). Mean gestational age at screening was 14.4 weeks. Mean venous plasma glucose was 131.6 ± 34.9 mg/dL and mean POCT glucose was 149.3 ± 27.7 mg/dL. Mean difference was 17.7 ± 19.4 mg/dL, corresponding to 16.8 ± 18.3%. POCT results were significantly correlated with venous plasma glucose (correlation coefficient 0.832, p < 0.001). GDM was diagnosed in 16 women (8.9%). At 140 mg/dL cut off, abnormal GCT was found in 37% by venous plasma glucose and 61% by POCT glucose results. Using 140 mg/dL cut off, POCT glucose has 97.1% sensitivity and 73.9% accuracy. At 165 mg/dL cut off, POCT glucose has 98.2% specificity and 82.8% accuracy.Conclusion: POCT capillary glucose testing could be considered as an alternative to conventional venous glucose testing for 50-g GCT for GDM screening using 140 and 165 mg/dL cut off values.